Polyvinylidene fluoride film used as battery diaphragm and preparation method thereof
Through non-solvent induced phase separation method and directional flow technology, the problems of cell separator pore size regulation and crystallinity are solved, and the high performance and long life of lithium/sodium ion batteries are achieved.
Patent Information
- Application Number
- CN202411468845.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The pore size of existing battery separators is difficult to control, the inconcentrated pore size distribution leads to dendrite growth, and the rapid film formation process leads to excessive crystallization of polymer films, limiting the improvement of battery performance.
Through non-solvent-induced phase separation method and directional flow technology, the pore size and distribution of polyvinylidene fluoride films are accurately controlled, the crystallinity is reduced, and the porous films with uniform pore size and centralized distribution are formed.
A uniform electroplating/peeling process of lithium/sodium ions is realized, which inhibits dendrites' growth, improves battery life and performance, and improves electrolyte absorption rate and ion migration performance.
Smart Images

Figure CN119241901A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyvinylidene fluoride film preparation, and in particular to a polyvinylidene fluoride film used as a battery separator and a preparation method thereof. Background Art
[0002] As a key component of the battery, the main function of the diaphragm is to isolate the positive electrode and the negative electrode to prevent the positive and negative electrodes from contacting and causing a short circuit in the battery. In addition, the diaphragm needs to absorb and retain the liquid electrolyte, and the diaphragm needs to be a porous structure to provide a channel for the migration of lithium / sodium ions. Therefore, the pore size and pore size distribution range of the diaphragm have an important influence on the performance of the battery. Too large a pore size will cause serious self-discharge of the battery, while too small a pore size will affect the efficiency of the solvation sheath formed by lithium / sodium ions in the liquid electrolyte passing through the diaphragm. In addition, uneven pore size distribution or too wide a pore size distribution range will lead to uneven plating / stripping of lithium ions and accelerate the growth of lithium dendrites. These properties related to the pore size of the diaphragm will further affect the life and safety performance of the battery.
[0003] At present, commercial battery separators are mainly PP separators. Although the pore size distribution range is relatively concentrated, due to the problem of pore-making process, the shape of the pores is an ellipse with a large aspect ratio (ratio of long diameter to short diameter). At present, porous separators are mainly obtained by electrostatic spinning or scraping. For example, Guanghai Chen et al. reported in "A Flexible Dual-Ion Battery Based on PVDF-HFP-Modified Gel Polymer Electrolyte with Excellent Cycling Performance and Superior Rate Capability, Advanced Energy Materials, 2018, 1801219" that a PVDF-HFP polymer membrane with a pore size of about 450nm was obtained by scraping. In 2021, Menglin Li et al. reported in “Enhanced the mechanical strength of polyimide (PI) nanofiber separator via PAALi binder for lithium ion battery, Composites Communications, 2021, 24, 100607” that a polyimide membrane with a pore size of 510 nm and a pore size distribution range of about ±100 nm was obtained by electrospinning. The membranes obtained by these two methods have the disadvantages of excessively large pore sizes and non-concentrated pore size distribution. The pore characteristics of the above-mentioned membranes are not conducive to the battery's requirements for long life and high safety performance. Therefore, a membrane with a suitable pore size and a concentrated pore size distribution range is very important for the life and safety performance of the battery.
[0004] The invention patent "A porous polymer membrane and its preparation method" with application number CN202410230391.X proposes a method for quickly preparing a polymer film, which may solve the problem of poor pore size and distribution quality existing in the above-mentioned other existing membrane-making technologies. However, one of the characteristics of the membrane-making method adopted in this invention is "fast film formation speed", which will affect the crystallinity of crystalline polymers such as polyvinylidene fluoride during the film-forming process. The faster the film-forming speed, the more likely the crystallinity of the polymer will be significantly improved. Taking crystalline polyvinylidene fluoride and its copolymers as an example, the crystallinity of polymer films prepared by traditional scraping or casting is generally low, generally around 30%, as reported in the literature "Enhancing piezoelectric properties of PVDF-HFP composite nanofibers with cellulose nanocrystals, Materials Today Communications, 2024, 39, 108872"; and the crystallinity of polyvinylidene fluoride membranes prepared by similar rapid film-forming methods as mentioned above may be very high. The process of polymer transformation from dissolved state to solid state at a very fast speed may be similar to the process of heating the polymer film at high temperature and then quickly annealing it in cold water in order to improve the crystallinity of the polymer film in traditional technology, as reported in the literature "Ultrahighβ-phase content poly(vinylidene fluoride) with relaxor-like ferroelectricity forhigh energy density capacitors, Nature Communications, 2019, 10, 4535". The increase in the crystallinity of polyvinylidene fluoride membrane is not conducive to its application in the field of lithium / sodium ion battery separators, which is not conducive to the wettability of polyvinylidene fluoride with electrolyte and the migration of lithium / sodium ions, thereby limiting the improvement of battery performance. Summary of the invention
[0005] In view of this, the present invention proposes a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, so as to solve the problems in the existing membrane making technology, that the pore size of the battery separator is difficult to control and the pore size distribution range is not concentrated enough, resulting in dendrite growth, and the rapid film forming process of the polymer solution causes the crystallinity of the crystalline polymer film to increase maliciously.
[0006] The technical solution of the present invention is achieved in this way:
[0007] In a first aspect, the present invention provides a method for preparing a polyvinylidene fluoride film used as a battery separator, comprising the following steps:
[0008] S1. Add 4 to 15 parts of polyvinylidene fluoride powder to 85 to 96 parts of an organic mixed solvent by weight, and stir to dissolve to obtain a uniform polyvinylidene fluoride solution;
[0009] S2. Directly spread the polyvinylidene fluoride solution on the surface of a liquid coagulation bath, solidify the spread solution into a film by a non-solvent-induced phase separation method, and dry at 23-27° C. to obtain a polyvinylidene fluoride film.
[0010] In the present invention, by precisely controlling the composition and film-forming conditions of the polyvinylidene fluoride solution, the pore size and distribution of the polyvinylidene fluoride film are precisely controlled, while avoiding the problem of excessive crystallinity caused by rapid film formation, so that the film has good electrolyte wettability and ion migration performance. Specifically, in step S1, by dissolving a specific proportion of polyvinylidene fluoride powder in an organic mixed solvent, the viscosity and phase separation behavior of the solution can be adjusted, thereby affecting the pore size and distribution of the final film; in step S2, a porous polyvinylidene fluoride film is prepared by a non-solvent induced phase separation method, and a film with a specific pore structure can be formed by making the polyvinylidene fluoride solution flow in a directional manner and solidifying it on the surface of a liquid coagulation bath. The non-solvent induced phase separation method uses the exchange between the solvent and the non-solvent to induce phase separation of the polymer solution. When the polyvinylidene fluoride solution contacts the coagulation bath (usually containing water), the solvent and the non-solvent are quickly exchanged, causing the polyvinylidene fluoride to precipitate from the solution and form a porous structure. By controlling the phase separation process, a porous film with uniform pore size and concentrated distribution is formed. Directed flow helps to form a uniform membrane structure and avoids the unevenness of pore size and distribution. Lower drying temperature can slow down the crystallization rate of polyvinylidene fluoride, which is beneficial to avoid excessive crystallinity, thereby maintaining good flexibility and electrolyte wettability of the film.
[0011] On the basis of the above technical solution, preferably, in step S1, the organic mixed solvent includes component A and component B, and in terms of mass percentage, component A accounts for 95-99.5% and component B accounts for 0.5-5%.
[0012] On the basis of the above technical solution, preferably, the component A is one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone, and the component B is petroleum ether.
[0013] Specifically, component A, as a good solvent, can effectively dissolve polyvinylidene fluoride powder, while component B, as a non-solvent, can reduce the solution's ability to dissolve polyvinylidene fluoride. The presence of component B can affect the crystallization behavior of polyvinylidene fluoride. By adjusting the ratio of component A to component B, the solubility of polyvinylidene fluoride in the solution can be precisely controlled, and the crystallization rate of polyvinylidene fluoride can be slowed down, which helps to avoid the problem of excessive crystallinity caused by rapid film formation, thereby maintaining good flexibility of the film and electrolyte wettability.
[0014] On the basis of the above technical solution, preferably, in step S1, the stirring and dissolving temperature is 20 to 35° C., and the time is 12 to 48 hours.
[0015] On the basis of the above technical scheme, preferably, in step S2, the liquid coagulation bath comprises component A and water, the volume ratio of component A to water is 0:100 to 37:63, and component A can be one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone.
[0016] Directed flow helps to form a uniform film, and the composition of the liquid coagulation bath (such as the ratio of component A to water) directly affects the pore formation process and film formation rate. When the polyvinylidene fluoride solution contacts the coagulation bath, the solvent in the solution exchanges with the non-solvent (water) in the coagulation bath. The presence of component A can adjust this exchange rate, thereby affecting the pore formation process. By adjusting the ratio of component A to water, the pore size and distribution can be precisely controlled. Higher water content usually leads to faster phase separation and larger pores; increasing the proportion of component A can slow down phase separation and help form smaller and evenly distributed pores.
[0017] In a second aspect, the present invention provides a polyvinylidene fluoride film, which is prepared by any of the preparation methods described above, and the polyvinylidene fluoride film is a porous film.
[0018] On the basis of the above technical solution, preferably, the pore size of the polyvinylidene fluoride film is 42 to 234 nm, the pore size distribution range is ±2 nm to ±26 nm, the porosity is 42% to 84%, and the Gurley value of the air permeability is 196 s / 100 mL to 856 s / 100 mL.
[0019] On the basis of the above technical solution, preferably, the thickness of the polyvinylidene fluoride film is 5.2 μm to 22.7 μm, and the crystallinity of the polyvinylidene fluoride film is 26% to 31%.
[0020] In a third aspect, the present invention provides an application of a polyvinylidene fluoride film, wherein the polyvinylidene fluoride film is used in a lithium ion battery or a sodium ion battery.
[0021] On the basis of the above technical solution, preferably, when the polyvinylidene fluoride film is used in a lithium ion battery, the electrolyte of the lithium ion battery is any one of the commercial electrolytes LB-266, LB-083 and LB-002; when the polyvinylidene fluoride film is used in a sodium ion battery, the electrolyte of the sodium ion battery is any one of the commercial electrolytes NC-021, NC-022, NC-004.
[0022] More preferably, electrolyte LB-266 satisfies the purity of 1M LiPF6 in DEC:DMC:EC=1:1:1Vol%with1%VC, electrolyte LB-083 satisfies the purity of 1M LiPF6 in DMC:EC:EMC=1:1:1Vol%with5%FEC, and electrolyte LB-002 satisfies the purity of 1M LiPF6 in DMC:EC:EMC=1:1:1Vol%. When polyvinylidene fluoride film is used in lithium-ion batteries as a battery separator, any one of the above electrolytes is used as a liquid lithium-ion battery electrolyte to assemble a Li||LFP button battery, and the capacity retention rate after 221 to 321 cycles at a charge and discharge rate of 1C reaches more than 79%.
[0023] More preferably, the electrolyte NC-021 satisfies the purity of 1M NaPF6 in EC:PC=1:1:1Vol%, the electrolyte NC-022 satisfies the purity of 1M NaPF6 in EC:PC=1:1:1Vol%with 2%FEC, and the electrolyte NC-004 satisfies the purity of 1MNaPF6 in EC:PC=1:1:1Vol%with 5%FEC. When the polyvinylidene fluoride film is used in a sodium ion battery as a battery separator, any one of the above electrolytes is used as a liquid sodium ion battery electrolyte to assemble into Na||PBAs button batteries, and the capacity retention rate after 308 to 356 cycles at a charge and discharge rate of 1C reaches more than 67%.
[0024] The polyvinylidene fluoride film used as a battery separator and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:
[0025] (1) The pore size of the polyvinylidene fluoride film prepared by the preparation method provided by the present invention is 42nm to 234nm, and the pore size distribution range is: ±2nm to ±26nm. The pore size is adjustable within a range suitable for practical applications, and the pore size distribution range is very concentrated, which can achieve a uniform electroplating / stripping process of lithium / sodium ions, inhibit the growth of dendrites, and obtain a lithium / sodium ion battery with longer life and higher performance;
[0026] (2) Compared with commercial PP separators, the polyvinylidene fluoride film obtained by the present invention has higher porosity and air permeability, which will increase the electrolyte absorption rate of the separator and is beneficial to improving the performance of the battery; the thickness of the polyvinylidene fluoride film is 5.2 μm to 22.7 μm, which is small in size and light in weight compared with commercial PP separators (thickness is generally 25 μm), and can be used for higher battery energy density;
[0027] (3) The present invention achieves precise control of the pore structure of the polyvinylidene fluoride film by regulating the ratio of component A (good solvent) and component B (non-solvent) in the organic mixed solvent and adopts a non-solvent induced phase separation combined with a directional flow film forming method, so that the prepared film has an ideal pore size and an extremely narrow distribution range, and reduces the crystallinity of the polyvinylidene fluoride film to 26% to 31%, which can better absorb electrolyte and promote ion migration. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 is a cycle performance diagram of the lithium ion battery in Example 1 at room temperature;
[0030] Figure 2 The cross-sectional SEM image and pore size distribution diagram of the polyvinylidene fluoride film of Example 2
[0031] Figure 3 This is a cycle performance diagram of the lithium ion battery of Example 2 at room temperature;
[0032] Figure 4 This is a cycle performance diagram of the sodium ion battery of Example 2 at room temperature;
[0033] Figure 5 This is a cycle performance diagram of the lithium ion battery of Example 3 at room temperature;
[0034] Figure 6 This is a cycle performance diagram of the lithium ion battery of Example 4 at room temperature;
[0035] Figure 7 The cross-sectional SEM image and pore size distribution diagram of the polyvinylidene fluoride film of Example 5;
[0036] Figure 8 This is a cycle performance diagram of the lithium ion battery of Example 5 at room temperature;
[0037] Fig. 9 This is a cycle performance diagram of the sodium ion battery of Example 5 at room temperature;
[0038] Fig.10 This is a cycle performance diagram of the lithium ion battery of Example 6 at room temperature;
[0039] Fig.11 This is a cycle performance diagram of the lithium ion battery of Example 7 at room temperature;
[0040] Fig.12 The cross-sectional SEM image and pore size distribution diagram of the polyvinylidene fluoride film of Example 8;
[0041] Fig.13 This is a cycle performance diagram of the lithium ion battery of Example 8 at room temperature;
[0042] Fig.14 This is a cycle performance diagram of the sodium ion battery of Example 8 at room temperature;
[0043] Fig.15 This is a cycle performance diagram of the lithium ion battery of Example 9 at room temperature;
[0044] Fig.16 This is a cycle performance diagram of the lithium ion battery of Comparative Example 1 at room temperature;
[0045] Fig.17 are the polyvinylidene fluoride film images of Comparative Examples 2, 4 and 6;
[0046] Fig.18 This is a cycle performance diagram of the lithium ion battery of Comparative Example 7 at room temperature;
[0047] Fig.19 The cross-sectional SEM image and pore size distribution diagram of the polyvinylidene fluoride film of Comparative Example 8;
[0048] Fig. 20 This is a cycle performance diagram of the lithium ion battery of Comparative Example 8 at room temperature;
[0049] Fig.21 This is a cycle performance diagram of the lithium ion battery of Comparative Example 9 at room temperature;
[0050] Fig. 22 The cross-sectional SEM image and pore size distribution diagram of the polyvinylidene fluoride film of Comparative Example 10;
[0051] Fig.23 This is a cycle performance diagram of the lithium ion battery of Comparative Example 10 at room temperature;
[0052] Fig.24 This is a cycle performance diagram of the sodium ion battery of Comparative Example 10 at room temperature;
[0053] Fig.25 This is a cross-sectional SEM image of the lithium-ion battery separator of Comparative Example 11;
[0054] Fig.26 This is a pore size distribution diagram of the lithium ion battery separator of Comparative Example 11;
[0055] Fig. 27 This is a cycle performance diagram of the lithium ion battery of Comparative Example 11 at room temperature. DETAILED DESCRIPTION
[0056] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0057] Example 1
[0058] This embodiment provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically includes the following steps:
[0059] S1, adding 4g of polyvinylidene fluoride powder to a mixed solvent of 96g of DMF and petroleum ether, wherein the petroleum ether accounts for 5.0% of the mixed solvent, stirring at 20°C for 12h to dissolve to obtain a uniform polyvinylidene fluoride solution;
[0060] S2, by non-solvent induced phase separation method, the polyvinylidene fluoride solution is directional flow, and in the liquid coagulation bath (volume ratio V 水 :V DMF =100:0) to solidify the surface and form a film to obtain a wet porous polyvinylidene fluoride film; the polyvinylidene fluoride film is dried at room temperature to obtain a porous polyvinylidene fluoride film for use.
[0061] The melting enthalpy ΔH of the polyvinylidene fluoride film can be measured by differential scanning calorimetry (DSC). f , and then calculate the crystallinity of the prepared polyvinylidene fluoride according to the following formula: c :
[0062]
[0063] In the formula, It refers to the melting enthalpy of polyvinylidene fluoride with a crystallinity of 100% (104.6 J / g).
[0064] After testing, the polyvinylidene fluoride film prepared in this embodiment has a crystallinity of 28.5%, an average thickness of 5.2 μm, a pore size of 52 nm, a pore size distribution range of ±8.6 nm, a porosity of 42%, and a Gurley value of air permeability of 196 s / 100 mL. Figure 1 It can be seen that the polyvinylidene fluoride film prepared in this embodiment is a porous film with a relatively uniform pore size distribution.
[0065] The polyvinylidene fluoride film was used as a lithium-ion battery separator, and a commercial electrolyte LB-266 (1M LiPF6in DEC:DMC:EC=1:1:1Vol%with 1%VC) was used as a liquid electrolyte to assemble a Li||LFP button cell. Figure 1 As shown, the capacity retention rate of the lithium-ion battery prepared in this embodiment after 305 cycles at a charge and discharge rate of 1C is 79.60%.
[0066] Example 2
[0067] This embodiment provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically includes the following steps:
[0068] S1. Add 4 g of polyvinylidene fluoride powder to a mixed solvent of 96 g of DMF and petroleum ether, wherein the petroleum ether accounts for 2.0% of the mixed solvent, and stir at 20° C. for 12 h to dissolve to obtain a uniform polyvinylidene fluoride solution;
[0069] S2, by non-solvent induced phase separation method, the polyvinylidene fluoride solution is directional flow, and in a liquid coagulation bath (volume ratio V 水 :V DMF =100:0 mixed solvent) to solidify into a film to obtain a porous polyvinylidene fluoride film; the polyvinylidene fluoride film is dried at room temperature to obtain a porous polyvinylidene fluoride film for use.
[0070] After testing, the polyvinylidene fluoride film prepared in this embodiment has a crystallinity of 30% and a thickness of 5.9 μm (eg Figure 2 As shown in a, Figure 2 a shows a cross-sectional SEM image of a polyvinylidene fluoride film, the pore size is 44 nm, and the pore size distribution range is: ±2.7 nm, (such as Figure 2 As shown in b, Figure 2 b shows the pore size distribution of the polyvinylidene fluoride film), the porosity is 43.5%, and the Gurley value of the air permeability is 203s / 100mL. Figure 2 As shown, the polyvinylidene fluoride membrane prepared in this embodiment is a porous membrane with relatively uniform pore size distribution.
[0071] The polyvinylidene fluoride film was used as a lithium-ion battery separator, and a commercial electrolyte LB-266 (1M LiPF6in DEC:DMC:EC=1:1:1Vol%with 1%VC) was used as a liquid electrolyte to assemble a Li||LFP button cell. Figure 3 As shown, the capacity retention rate of the lithium-ion battery prepared in this embodiment after 254 cycles at a charge and discharge rate of 1C is 91.31%.
[0072] The above polyvinylidene fluoride film was used as a sodium ion battery separator, and the commercial electrolyte NC-022 (1M NaPF6in EC:PC=1:1:1Vol%with 2%FEC) was used as the liquid electrolyte to assemble Na||PBAs button cells, such as Figure 4 As shown, the sodium ion battery prepared in this embodiment has a capacity retention rate of 67.20% after 308 cycles at a charge and discharge rate of 1C.
[0073] Example 3
[0074] This embodiment provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically includes the following steps:
[0075] S1. Add 4 g of polyvinylidene fluoride powder to a mixed solvent of 96 g of DMF and petroleum ether, wherein the petroleum ether accounts for 0.5% of the mixed solvent, and stir at 20° C. for 12 h to dissolve to obtain a uniform polyvinylidene fluoride solution;
[0076] S2, by non-solvent induced phase separation method, the polyvinylidene fluoride solution is directional flow, and in a liquid coagulation bath (volume ratio V 水 :V DMF =100:0 mixed solvent) to solidify into a film to obtain a porous polyvinylidene fluoride film; the polyvinylidene fluoride film is dried at room temperature to obtain a porous polyvinylidene fluoride film for use.
[0077] After testing, the polyvinylidene fluoride film prepared in this embodiment has a crystallinity of 31%, a thickness of 7.1 μm, a pore size of 42 nm, a pore size distribution range of ±2.1 nm, a porosity of 44.5%, and a Gurley value of air permeability of 206 s / 100 mL.
[0078] The polyvinylidene fluoride film was used as a lithium-ion battery separator, and a commercial electrolyte LB-266 (1M LiPF6in DEC:DMC:EC=1:1:1Vol%with 1%VC) was used as a liquid electrolyte to assemble a Li||LFP button cell. Figure 5As shown, the capacity retention rate of the lithium-ion battery prepared in this embodiment after 261 cycles at a charge and discharge rate of 1C is 78.09%.
[0079] Example 4
[0080] This embodiment provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically includes the following steps:
[0081] S1, adding 8g of polyvinylidene fluoride powder to a mixed solvent of 92g of DMF and petroleum ether, wherein the petroleum ether accounts for 5.0% of the mixed solvent, stirring at 20°C for 48h to dissolve to obtain a uniform polyvinylidene fluoride solution;
[0082] S2, by non-solvent induced phase separation method, the polyvinylidene fluoride solution is directional flow, and in a liquid coagulation bath (volume ratio V 水 :V NMP =82:18 mixed solvent) to solidify into a film to obtain a porous polyvinylidene fluoride film; the polyvinylidene fluoride film is dried at room temperature to obtain a porous polyvinylidene fluoride film for use.
[0083] After testing, the polyvinylidene fluoride film prepared in this embodiment has a crystallinity of 27%, a thickness of 10.7 μm, a pore size of 114 nm, a pore size distribution range of ±15.7 nm, a porosity of 56%, and a Gurley value of air permeability of 374 s / 100 mL.
[0084] The polyvinylidene fluoride film was used as a lithium-ion battery separator, and a commercial electrolyte LB-266 (1M LiPF6in DEC:DMC:EC=1:1:1Vol%with 1%VC) was used as a liquid electrolyte to assemble a Li||LFP button cell. Figure 6 As shown, the capacity retention rate of the lithium-ion battery prepared in this embodiment after 300 cycles at a charge and discharge rate of 1C is 83.04%.
[0085] Example 5
[0086] This embodiment provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically includes the following steps:
[0087] S1, adding 8g of polyvinylidene fluoride powder to a mixed solvent of 92g of DMF and petroleum ether, wherein the petroleum ether accounts for 2.0% of the mixed solvent, stirring at 20°C for 48h to dissolve to obtain a uniform polyvinylidene fluoride solution;
[0088] S2, by non-solvent induced phase separation method, the polyvinylidene fluoride solution is directional flow, and in a liquid coagulation bath (volume ratio V水 :V NMP =82:18) to form a film to obtain a porous polyvinylidene fluoride film; the polyvinylidene fluoride film is dried at room temperature to obtain a porous polyvinylidene fluoride film for use.
[0089] After testing, the polyvinylidene fluoride film prepared in this embodiment has a crystallinity of 29% and a thickness of 11.6 μm (eg Figure 7 As shown in a, Figure 7 a shows a cross-sectional SEM image of a polyvinylidene fluoride film, the pore size is 96 nm, and the pore size distribution range is: ±1.8 nm (such as Figure 7 As shown in b, Figure 7 b shows the pore size distribution of the polyvinylidene fluoride film), the porosity is 58%, and the Gurley value of the air permeability is 379s / 100mL. Figure 7 It can be seen that the polyvinylidene fluoride film prepared in this embodiment is a porous film with a relatively uniform pore size distribution.
[0090] The polyvinylidene fluoride film was used as a lithium-ion battery separator, and a commercial electrolyte LB-266 (1M LiPF6in DEC:DMC:EC=1:1:1Vol%with 1%VC) was used as a liquid electrolyte to assemble a Li||LFP button cell. Figure 8 As shown, the capacity retention rate of the lithium-ion battery prepared in this embodiment after 402 cycles at a charge and discharge rate of 1C is 78.84%.
[0091] The above polyvinylidene fluoride film was used as a sodium ion battery separator, and the commercial electrolyte NC-022 (1M NaPF6in EC:PC=1:1:1Vol%with 2%FEC) was used as the liquid electrolyte to assemble Na||PBAs button cells, such as Fig. 9 As shown, the sodium ion battery prepared in this embodiment has a capacity retention rate of 82.10% after 327 cycles at a charge and discharge rate of 1C.
[0092] Example 6
[0093] This embodiment provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically includes the following steps:
[0094] S1, adding 8g of polyvinylidene fluoride powder to a mixed solvent of 92g of DMF and petroleum ether, wherein the petroleum ether accounts for 0.5% of the mixed solvent, stirring at 20°C for 48h to dissolve to obtain a uniform polyvinylidene fluoride solution;
[0095] S2, by non-solvent induced phase separation method, the polyvinylidene fluoride solution is directional flow, and in a liquid coagulation bath (volume ratio V水 :V NMP =82:18 mixed solvent) to solidify into a film to obtain a porous polyvinylidene fluoride film; the polyvinylidene fluoride film is dried at room temperature to obtain a porous polyvinylidene fluoride film for use.
[0096] After testing, the polyvinylidene fluoride film prepared in this embodiment has a crystallinity of 30.5%, a thickness of 13.5 μm, a pore size of 91 nm, a pore size distribution range of ±2.1 nm, a porosity of 62%, and a Gurley value of air permeability of 387 s / 100 mL.
[0097] The polyvinylidene fluoride film was used as a lithium-ion battery separator, and a commercial electrolyte LB-266 (1M LiPF6in DEC:DMC:EC=1:1:1Vol%with 1%VC) was used as a liquid electrolyte to assemble a Li||LFP button cell. Fig.10 As shown, the capacity retention rate of the lithium-ion battery prepared in this embodiment after 321 cycles at a charge and discharge rate of 1C is 83.30%.
[0098] Example 7
[0099] This embodiment provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically includes the following steps:
[0100] S1. Add 15 g of polyvinylidene fluoride powder to a mixed solvent of 85 g of DMF and petroleum ether, wherein the petroleum ether accounts for 5.0% of the mixed solvent, and stir at 35° C. for 36 h to dissolve to obtain a uniform polyvinylidene fluoride solution;
[0101] S2, by non-solvent induced phase separation method, the polyvinylidene fluoride solution is directional flow, and in a liquid coagulation bath (volume ratio V 水 :V DMF =63:37 mixed solvent) to solidify into a film to obtain a porous polyvinylidene fluoride film; the polyvinylidene fluoride film is dried at room temperature to obtain a porous polyvinylidene fluoride film for use.
[0102] After testing, the polyvinylidene fluoride film prepared in this embodiment has a crystallinity of 26%, a thickness of 20.7 μm, a pore size of 234 nm, a pore size distribution range of ±25.8 nm, a porosity of 78%, and a Gurley value of air permeability of 832 s / 100 mL.
[0103] The polyvinylidene fluoride film was used as a lithium-ion battery separator, and a commercial electrolyte LB-266 (1M LiPF6in DEC:DMC:EC=1:1:1Vol%with 1%VC) was used as a liquid electrolyte to assemble a Li||LFP button cell. Fig.11 As shown, the capacity retention rate of the lithium-ion battery prepared in this embodiment after 507 cycles at a charge and discharge rate of 1C is 80.51%.
[0104] Example 8
[0105] This embodiment provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically includes the following steps:
[0106] S1. Add 15 g of polyvinylidene fluoride powder to a mixed solvent of 85 g of DMF and petroleum ether, wherein the petroleum ether accounts for 2.0% of the mixed solvent, and stir at 35° C. for 36 h to dissolve to obtain a uniform polyvinylidene fluoride solution;
[0107] S2, by non-solvent induced phase separation method, the polyvinylidene fluoride solution is directional flow, and in a liquid coagulation bath (volume ratio V 水 :V DMF =63:37 mixed solvent) to solidify into a film to obtain a porous polyvinylidene fluoride film; the polyvinylidene fluoride film is dried at room temperature to obtain a porous polyvinylidene fluoride film for use.
[0108] After testing, the polyvinylidene fluoride film prepared in this embodiment has a crystallinity of 27.5% and a thickness of 21.6 μm (eg Fig.12 As shown in a, Fig.12 a shows a cross-sectional SEM image of a polyvinylidene fluoride film, the pore size is 214 nm, and the pore size distribution range is: ±3.8 nm (such as Fig.12 As shown in b, Fig.12 b shows the pore size distribution of the polyvinylidene fluoride film), the porosity is 81%, and the Gurley value of the air permeability is 841s / 100mL. Fig.12 It can be seen that the polyvinylidene fluoride film prepared in this embodiment is a porous film with a relatively uniform pore size distribution.
[0109] The polyvinylidene fluoride film was used as a lithium-ion battery separator, and a commercial electrolyte LB-266 (1M LiPF6in DEC:DMC:EC=1:1:1Vol%with 1%VC) was used as a liquid electrolyte to assemble a Li||LFP button cell. Fig.13 As shown, the capacity retention rate of the lithium-ion battery prepared in this embodiment after 534 cycles at a charge and discharge rate of 1C is 90.84%.
[0110] The above polyvinylidene fluoride film was used as a sodium ion battery separator, and the commercial electrolyte NC-022 (1M NaPF6in EC:PC=1:1:1Vol%with 2%FEC) was used as the liquid electrolyte to assemble Na||PBAs button cells, such as Fig.14 As shown, the sodium ion battery prepared in this embodiment has a capacity retention rate of 82.80% after 356 cycles at a charge and discharge rate of 1C.
[0111] Example 9
[0112] This embodiment provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically includes the following steps:
[0113] S1. Add 15 g of polyvinylidene fluoride powder to a mixed solvent of 85 g of DMF and petroleum ether, wherein the petroleum ether accounts for 0.5% of the mixed solvent, and stir at 35° C. for 36 h to dissolve to obtain a uniform polyvinylidene fluoride solution;
[0114] S2, by non-solvent induced phase separation method, the polyvinylidene fluoride solution is directional flow, and in a liquid coagulation bath (volume ratio V 水 :V DMF =63:37 mixed solvent) to solidify into a film to obtain a porous polyvinylidene fluoride film; the polyvinylidene fluoride film is dried at room temperature to obtain a porous polyvinylidene fluoride film for use.
[0115] After testing, the polyvinylidene fluoride film prepared in this embodiment has a crystallinity of 29%, a thickness of 22.7 μm, a pore size of 211 nm, a pore size distribution range of ±3.1 nm, a porosity of 84%, and a Gurley value of air permeability of 856 s / 100 mL.
[0116] The polyvinylidene fluoride film was used as a lithium-ion battery separator, and a commercial electrolyte LB-266 (1M LiPF6in DEC:DMC:EC=1:1:1Vol%with 1%VC) was used as a liquid electrolyte to assemble a Li||LFP button cell. Fig.15 As shown, the capacity retention rate of the lithium-ion battery prepared in this embodiment after 397 cycles at a charge and discharge rate of 1C is 81.91%.
[0117] Comparative Example 1
[0118] This comparative example provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically comprises the following steps:
[0119] S1. Add 4 g of polyvinylidene fluoride powder to a mixed solvent of 96 g of DMF and petroleum ether, wherein the petroleum ether accounts for 0.2% of the mixed solvent, and stir at 20° C. for 12 h to dissolve to obtain a uniform polyvinylidene fluoride solution;
[0120] S2, by non-solvent induced phase separation method, the polyvinylidene fluoride solution is directional flow, and in a liquid coagulation bath (volume ratio V 水 :V DMF =100:0 mixed solvent) to solidify into a film to obtain a porous polyvinylidene fluoride film; the polyvinylidene fluoride film is dried at room temperature to obtain a porous polyvinylidene fluoride film for use.
[0121] After testing, the polyvinylidene fluoride film prepared in this comparative example has a crystallinity of 38%, a thickness of 8.4 μm, a pore size of 41 nm, a pore size distribution range of ±2.0 nm, a porosity of 45%, and a Gurley value of air permeability of 208 s / 100 mL.
[0122] The polyvinylidene fluoride film was used as a lithium-ion battery separator, and a commercial electrolyte LB-266 (1M LiPF6in DEC:DMC:EC=1:1:1Vol%with 1%VC) was used as a liquid electrolyte to assemble a Li||LFP button cell. Fig.16 As shown, the capacity retention rate of the lithium-ion battery prepared in this comparative example after 211 cycles at a charge and discharge rate of 1C is 84.50%.
[0123] Comparative Example 2
[0124] This comparative example provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically comprises the following steps:
[0125] S1. Add 4g of polyvinylidene fluoride powder to a mixed solvent of 96g of DMF and petroleum ether, wherein the petroleum ether accounts for 6.0% of the mixed solvent, and stir at 20°C for 12h to dissolve, and the solution precipitates. Fig.17 As shown in (a), this comparative example does not produce a complete polyvinylidene fluoride film because the organic solvent of component B is petroleum ether, which can hinder the dissolution of polyvinylidene fluoride and has low solubility with the organic solvent of component A and is insoluble in water, which can greatly slow down the diffusion of the organic solvent in the polyvinylidene fluoride solution into the coagulation bath.
[0126] Comparative Example 3
[0127] This comparative example provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically comprises the following steps:
[0128] S1, adding 8g of polyvinylidene fluoride powder to a mixed solvent of 92g of DMF and petroleum ether, wherein the petroleum ether accounts for 0.2% of the mixed solvent, stirring at 20°C for 48h to dissolve to obtain a uniform polyvinylidene fluoride solution;
[0129] S2, by non-solvent induced phase separation method, the polyvinylidene fluoride solution is directional flow, and in a liquid coagulation bath (volume ratio V 水 :V NMP =82:18 mixed solvent) to solidify into a film to obtain a porous polyvinylidene fluoride film; the polyvinylidene fluoride film is dried at room temperature to obtain a porous polyvinylidene fluoride film for use.
[0130] After testing, the polyvinylidene fluoride film prepared in this comparative example has a crystallinity of 36.5%, a thickness of 14.1 μm, a pore size of 82 nm, a pore size distribution range of ±2.2 nm, a porosity of 64%, and a Gurley value of air permeability of 391 s / 100 mL.
[0131] Comparative Example 4
[0132] This comparative example provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically comprises the following steps:
[0133] S1. Add 8g of polyvinylidene fluoride powder to a mixed solvent of 92g of DMF and petroleum ether, wherein the petroleum ether accounts for 6.0% of the mixed solvent, and stir at 20°C for 48h to dissolve, and the solution precipitates. Fig.17 As shown in (b), this comparative example did not produce a complete polyvinylidene fluoride film because the organic solvent of component B is petroleum ether, which can hinder the dissolution of polyvinylidene fluoride and has low miscibility with the organic solvent of component A and is insoluble in water, which can greatly slow down the diffusion of the organic solvent in the polyvinylidene fluoride solution into the coagulation bath.
[0134] Comparative Example 5
[0135] This comparative example provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically comprises the following steps:
[0136] S1. Add 15 g of polyvinylidene fluoride powder to a mixed solvent of 85 g of DMF and petroleum ether, wherein the petroleum ether accounts for 0.2% of the mixed solvent, and stir at 35° C. for 36 h to dissolve to obtain a uniform polyvinylidene fluoride solution;
[0137] S2, by non-solvent induced phase separation method, the polyvinylidene fluoride solution is directional flow, and in a liquid coagulation bath (volume ratio V 水 :V DMF=63:37 mixed solvent) to solidify into a film to obtain a porous polyvinylidene fluoride film; the polyvinylidene fluoride film is dried at room temperature to obtain a porous polyvinylidene fluoride film for use.
[0138] After testing, the polyvinylidene fluoride film prepared in this comparative example has a crystallinity of 35%, a thickness of 23.4 μm, a pore size of 206 nm, a pore size distribution range of ±2.8 nm, a porosity of 82%, and a Gurley value of air permeability of 841 s / 100 mL.
[0139] Comparative Example 6
[0140] This comparative example provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically comprises the following steps:
[0141] S1. Add 15g of polyvinylidene fluoride powder to a mixed solvent of 85g of DMF and petroleum ether, wherein the petroleum ether accounts for 6.0% of the mixed solvent, and stir at 35°C for 36h to dissolve, and the solution precipitates. Fig.17 As shown in (c), this comparative example did not produce a complete polyvinylidene fluoride film because the organic solvent of component B is petroleum ether, which can hinder the dissolution of polyvinylidene fluoride and has low miscibility with the organic solvent of component A and is insoluble in water, which can greatly slow down the diffusion of the organic solvent in the polyvinylidene fluoride solution into the coagulation bath.
[0142] Comparative Example 7
[0143] This comparative example provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically comprises the following steps:
[0144] S1. Add 4 g of polyvinylidene fluoride powder into 96 g of DMF and stir at 20°C for 12 h to dissolve to obtain a uniform polyvinylidene fluoride solution;
[0145] S2, by non-solvent induced phase separation method, the polyvinylidene fluoride solution is directional flow, and in a liquid coagulation bath (volume ratio V 水 :V DMF =100:0 mixed solvent) to solidify into a film to obtain a porous polyvinylidene fluoride film; the polyvinylidene fluoride film is dried at room temperature to obtain a porous polyvinylidene fluoride film for use.
[0146] After testing, the polyvinylidene fluoride film prepared in this comparative example has a crystallinity of 51%, a thickness of 9.3 μm, a pore size of 53 nm, a pore size distribution range of ±1.9 nm, a porosity of 46%, and a Gurley value of air permeability of 228 s / 100 mL.
[0147] The polyvinylidene fluoride film was used as a lithium-ion battery separator, and a commercial electrolyte LB-266 (1M LiPF6in DEC:DMC:EC=1:1:1Vol%with 1%VC) was used as a liquid electrolyte to assemble a Li||LFP button cell. Fig.18 As shown, the capacity retention rate of the lithium-ion battery prepared in this comparative example after 297 cycles at a charge and discharge rate of 1C is 58.27%.
[0148] Comparative Example 8
[0149] This comparative example provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically comprises the following steps:
[0150] S1. Add 8 g of polyvinylidene fluoride powder into 92 g of DMF and stir at 20°C for 48 h to dissolve to obtain a uniform polyvinylidene fluoride solution;
[0151] S2, by non-solvent induced phase separation method, the polyvinylidene fluoride solution is directional flow, and in a liquid coagulation bath (volume ratio V 水 :V NMP =82:18 mixed solvent) to solidify into a film to obtain a porous polyvinylidene fluoride film; the polyvinylidene fluoride film is dried at room temperature to obtain a porous polyvinylidene fluoride film for use.
[0152] After testing, the polyvinylidene fluoride film prepared in this comparative example has a crystallinity of 48% and a thickness of 14.6 μm (eg Fig.19 As shown in a, Fig.19 a shows a cross-sectional SEM image of a polyvinylidene fluoride film, the pore size is 148 nm, and the pore size distribution range is: ±3.3 nm (such as Fig.19 As shown in b, Fig.19 b shows the pore size distribution of the polyvinylidene fluoride film), the porosity is 69%, and the Gurley value of the air permeability is 391s / 100mL. Fig.19 As shown, the polyvinylidene fluoride film prepared in this comparative example has a uniform pore size distribution.
[0153] The polyvinylidene fluoride film was used as a lithium-ion battery separator, and a commercial electrolyte LB-266 (1M LiPF6in DEC:DMC:EC=1:1:1Vol%with 1%VC) was used as a liquid electrolyte to assemble a Li||LFP button cell. Fig. 20 As shown, the capacity retention rate of the lithium-ion battery prepared in this comparative example after 282 cycles at a charge and discharge rate of 1C is 68.84%.
[0154] Comparative Example 9
[0155] This comparative example provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically comprises the following steps:
[0156] S1. Add 15 g of polyvinylidene fluoride powder into 85 g of DMF and stir at 35°C for 36 h to dissolve to obtain a uniform polyvinylidene fluoride solution;
[0157] S2, by non-solvent induced phase separation method, the polyvinylidene fluoride solution is directional flow, and in a liquid coagulation bath (volume ratio V 水 :V DMF =63:37 mixed solvent) to solidify into a film to obtain a porous polyvinylidene fluoride film; the polyvinylidene fluoride film is dried at room temperature to obtain a porous polyvinylidene fluoride film for use.
[0158] After testing, the polyvinylidene fluoride film prepared in this comparative example has a crystallinity of 45%, a thickness of 23.7 μm, a pore size of 202 nm, a pore size distribution range of ±3.5 nm, a porosity of 88%, and a Gurley value of air permeability of 868 s / 100 mL.
[0159] The polyvinylidene fluoride film was used as a lithium-ion battery separator, and a commercial electrolyte LB-266 (1M LiPF6in DEC:DMC:EC=1:1:1Vol%with 1%VC) was used as a liquid electrolyte to assemble a Li||LFP button cell. Fig.21 As shown, the capacity retention rate of the lithium-ion battery prepared in this comparative example after 255 cycles at a charge and discharge rate of 1C is 78.73%.
[0160] Comparative Example 10
[0161] This comparative example provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically comprises the following steps:
[0162] S1. Add 15 g of polyvinylidene fluoride powder into 85 g of DMF and stir at 35°C for 48 h to dissolve to obtain a uniform polyvinylidene fluoride solution;
[0163] S2. The obtained polyvinylidene fluoride solution is scraped into a 100 μm liquid film by a scraping method, and then placed in a liquid coagulation bath (volume ratio V 水 :V DMF =67:37 mixed solvent) to solidify into a film to obtain a porous polyvinylidene fluoride film; the polyvinylidene fluoride film is dried at room temperature to obtain a porous polyvinylidene fluoride film for use.
[0164] After testing, the polyvinylidene fluoride film prepared in this comparative example has a crystallinity of 35% and a thickness of 19.5 μm (eg Fig. 22 As shown in a, Fig. 22 a shows a cross-sectional SEM image of a polyvinylidene fluoride film, the pore size is 586 nm, and the pore size distribution range is: ±63.2 nm (such as Fig. 22 As shown in b, Fig. 22 b shows the pore size distribution of the polyvinylidene fluoride film), the porosity is 81%, and the Gurley value of the air permeability is 856s / 100mL. Fig. 22 It can be seen that the blade-coated polyvinylidene fluoride film is a multi-porous structure with coexistence of finger-like pores and honeycomb-like pores, which is not conducive to inhibiting dendrite growth, and the concentration degree of pore size distribution is obviously deviated.
[0165] The polyvinylidene fluoride film was used as a lithium-ion battery separator, and a commercial electrolyte LB-266 (1M LiPF6in DEC:DMC:EC=1:1:1Vol%with 1%VC) was used as a liquid electrolyte to assemble a Li||LFP button cell. Fig.23 As shown, the capacity retention rate of the lithium-ion battery prepared in this comparative example after 300 cycles at a charge and discharge rate of 1C is 36.19%.
[0166] The above polyvinylidene fluoride film was used as a sodium ion battery separator, and the commercial electrolyte NC-022 (1M NaPF6in EC:PC=1:1:1Vol%with 2%FEC) was used as the liquid electrolyte to assemble Na||PBAs button cells, such as Fig.24 As shown, the sodium ion battery prepared in this comparative example has a capacity retention rate of 58.46% after 297 cycles at a charge and discharge rate of 1C.
[0167] Comparative Example 11
[0168] This comparative example provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically comprises the following steps:
[0169] Commercial PP containing Al2O3 coating was used as lithium-ion battery separator (Al2O3@PP, Celgard, LLC), such as Fig.25 , Fig.26 As shown, Fig.25 a shows the SEM image of the cross section of a commercial PP separator. Fig.25 b shows a partially enlarged SEM image of the cross section of a commercial PP separator. Fig.25 It can be seen that although the commercial PP membrane is a porous membrane, further observation through the locally enlarged c figure shows that the pore size distribution of the commercial PP membrane is not uniform enough, and the size difference between large pores and small pores is large. Fig.26The pore size distribution of the commercial PP separator is shown in Figure 1. It can be seen that the concentration of the pore size distribution is significantly deviated. The commercial electrolyte LB-266 (1M LiPF6 in DEC:DMC:EC=1:1:1Vol%with 1%VC) was used as the liquid electrolyte to assemble a 79.6Li||LFP button cell, as shown in Figure 1. Fig. 27 As shown, the capacity retention rate of the lithium-ion battery prepared in this comparative example after 200 cycles at a charge and discharge rate of 1 C is 9.82%. It should be pointed out that after 190 cycles, the specific capacity drops drastically, indicating that the life of this battery is 190 cycles.
[0170] Comparative Example 12
[0171] This comparative example provides a polyvinylidene fluoride film used as a battery separator and a preparation method thereof, which specifically comprises the following steps:
[0172] S1, adding 16g of polyvinylidene fluoride powder to a mixed solvent of 84g of DMF and petroleum ether, wherein the petroleum ether accounts for 5.0% of the mixed solvent, stirring at 20°C for 12h to dissolve to obtain a uniform polyvinylidene fluoride solution;
[0173] S2, by non-solvent induced phase separation method, the polyvinylidene fluoride solution is directional flow, and in the liquid coagulation bath (volume ratio V 水 :V DMF =100:0-63:37) surface solidification film, the surface of the polyvinylidene fluoride polymer liquid film has some liquid polymer that is not completely solidified, and a completely solidified uniform polyvinylidene fluoride film cannot be obtained.
[0174] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a polyvinylidene fluoride film used as a battery separator, characterized in that: The following steps are involved: S1. Add 4 to 15 parts of polyvinylidene fluoride powder to 85 to 96 parts of an organic mixed solvent by weight, and stir to dissolve to obtain a uniform polyvinylidene fluoride solution; S2. Directly spread the polyvinylidene fluoride solution on the surface of a liquid coagulation bath, solidify the spread solution into a film by a non-solvent-induced phase separation method, and dry at 23-27° C. to obtain a polyvinylidene fluoride film.
2. The method for preparing a polyvinylidene fluoride film used as a battery separator according to claim 1, characterized in that: In step S1, the organic mixed solvent includes component A and component B, and in terms of mass percentage, component A accounts for 95-99.5% and component B accounts for 0.5-5%.
3. The method for preparing a polyvinylidene fluoride film used as a battery separator according to claim 2, characterized in that: The component A is one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone, and the component B is petroleum ether.
4. The method for preparing a polyvinylidene fluoride film for use as a battery separator according to claim 1, characterized in that: In step S1, the stirring and dissolving temperature is 20 to 35° C. and the time is 12 to 48 hours.
5. The method for preparing a polyvinylidene fluoride film used as a battery separator according to claim 3, characterized in that: In step S2, the liquid coagulation bath includes component A and water, and the volume ratio of component A to water is 0:100 to 37:
63.
6. A polyvinylidene fluoride film, characterized in that: The polyvinylidene fluoride film is prepared by the preparation method according to any one of claims 1 to 5, and the polyvinylidene fluoride film is a porous film.
7. A polyvinylidene fluoride film as claimed in claim 6, characterized in that: The pore size of the polyvinylidene fluoride film is 42-234 nm, the pore size distribution range is ±2 nm-±26 nm, the porosity is 42%-84%, and the Gurley value of the air permeability is 196 s / 100 mL-856 s / 100 mL.
8. The polyvinylidene fluoride film according to claim 6, characterized in that: The thickness of the polyvinylidene fluoride film is 5.2 μm to 22.7 μm, and the crystallinity of the polyvinylidene fluoride film is 26% to 31%.
9. The use of a polyvinylidene fluoride film according to any one of claims 6 to 8, characterized in that: The polyvinylidene fluoride film is used for lithium ion batteries or sodium ion batteries.
10. The use of a polyvinylidene fluoride film as claimed in claim 9, characterized in that: When the polyvinylidene fluoride film is used in a lithium ion battery, the electrolyte of the lithium ion battery is any one of the commercial electrolytes LB-266, LB-083 and LB-002; when the polyvinylidene fluoride film is used in a sodium ion battery, the electrolyte of the sodium ion battery is any one of the commercial electrolytes NC-021, NC-022 and NC-004.
Citation Information
Patent Citations
PVDF (Polyvinylidene Fluoride) film for water treatment and preparation method thereof
CN115121133A
Porous polyvinylidene fluoride membrane for water treatment, and method for producing porous polyvinylidene fluoride membrane for water treatment
JP2016183301A
